APPLICATION OF INTERNATIONAL STANDARDS OF FINANCIAL REPORTING IN ELECTRIC ENERGY SUPPLY ENTERPRISES (World Bulletin of Management and Law, 2023)
This article delves into the critical application of international standards of financial reporting within the context of electric energy supply enterprises. In an era of globalization and interconnected economies, adherence to internationally recognized financial reporting standards is crucial for ensuring transparency, accountability, and effective management. The article explores the challenges and benefits of implementing these standards, highlighting their impact on financial decision-making and the overall sustainability of electric energy supply enterprises.